Nobelpreisträgerinnen 14 Schriftstellerinnen im Porträt - Olk, Claudia; Zepp, Susanne (De Gruyter, 2019)
This volume presents the 14 female winners of the Nobel Prize in Literature, e.g. Lagerlöf, Sachs, Jelinek, Müller, Munro. Contributions offers exemplary readings of chosen works, while outlining the intellectual profile of each author. They also tackle the questions of female writing and canon formation, and interrogate the conditions and contradictions of artistic creativity.